2002
DOI: 10.1136/jnnp.72.6.701
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural disorders, Parkinson's disease and subthalamic stimulation

Abstract: Objective: to analyse 24 parkinsonian patients successfully treated by bilateral STN stimulation for the presence of behavioural disorders. Method: patients were evaluated retrospectively for adjustment disorders (social adjustment scale, SAS), psychiatric disorders (comparison of the results of psychiatric interview and the mini international neuropsychiatric inventory) and personality changes (IOWA scale of personality changes). Results: parkinsonian motor disability was improved by 69.5% and the levodopa eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
359
3
31

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(402 citation statements)
references
References 27 publications
9
359
3
31
Order By: Relevance
“…For example, Baunez and colleagues reported that bilateral STN lesions enhance motivation for food, as measured by progressive ratio performance and conditioned place preference (Baunez et al, 2002(Baunez et al, , 2005. Furthermore, HFS of the STN, which is thought to mimic ablation of the STN by inducing depolarization block (Benazzouz et al, 1993(Benazzouz et al, , 1995(Benazzouz et al, , 2000Lozano et al, 2002) (but see Garcia et al, 2005), enhances motivation and decreases apathy and also increases the therapeutic potency of the dopamine-enhancing drug L-3,4-dihydroxyphenylalanine (L-DOPA) in patients with Parkinson's disease (Limousin et al, 1998;Houeto et al, 2002;Funkiewiez et al, 2003;Ashkan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baunez and colleagues reported that bilateral STN lesions enhance motivation for food, as measured by progressive ratio performance and conditioned place preference (Baunez et al, 2002(Baunez et al, , 2005. Furthermore, HFS of the STN, which is thought to mimic ablation of the STN by inducing depolarization block (Benazzouz et al, 1993(Benazzouz et al, , 1995(Benazzouz et al, , 2000Lozano et al, 2002) (but see Garcia et al, 2005), enhances motivation and decreases apathy and also increases the therapeutic potency of the dopamine-enhancing drug L-3,4-dihydroxyphenylalanine (L-DOPA) in patients with Parkinson's disease (Limousin et al, 1998;Houeto et al, 2002;Funkiewiez et al, 2003;Ashkan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven of them 3,22,36,52,61,67,69,70,73,76,78 presented data in a non-comparable way, with a total of 52 references allowing quantitative analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Otros autores, por el contrario, han referido la aparición de ICD en pacientes tratados con DBS a pesar de la reducción de agonistas DA 49,72,104 . Por último en otros estudios realizados, la estimulación del núcleo subtalámico en pacientes jóvenes, aumentaría el riesgo de desarrollar ICD y en este contexto, no únicamente existiría un incremento en presentar un cuadro de impulsividad, sino también un mayor riesgo de suicidio 12,55,98,103,104,119 .…”
Section: Cirugía De La Ep Aspectos Motores Y No Motoresunclassified